Музика, поезія й танець у хореодрамі Віктора Тиможинського Неминуча - Коменда, О.; Дужич-Ніколайчук, В. (Студії мистецтвознавчі, 2007)
In this article the particularities of the genre and dramaturgical resolving of the choreo-drama "Inevitable" written by V. Tymozhynsky is being overlooked as the most original composition of Ukrainian post-modern art. Studying a problematic of musical, chorographical and poetical text, authors came to the conclusion, that music, poetic and choreographic elements are an independent artistic creativity. In the conditions of such architectonical-dramaturgical polytext their junction takes place with help of row of musical, poetical and chorographical symbols, which are giving to the composition features of the symbolic drama.